2004
DOI: 10.1021/bi048815y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the U6 RNA Intramolecular Stem−Loop:  A Base Flipping Conformational Change,

Abstract: The U6 RNA intramolecular stem-loop (ISL) structure is an essential component of the spliceosome and binds a metal ion required for pre-messenger RNA splicing. The metal binding internal loop region of the stem contains a partially protonated C67-(+)A79 base pair (pK(a) = 6.5) and an unpaired U80 nucleotide that is stacked within the helix at pH 7.0. Here, we determine that protonation occurs with an exchange lifetime of approximately 20 micros and report the solution structures of the U6 ISL at pH 5.7. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
119
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(143 citation statements)
references
References 61 publications
23
119
1
Order By: Relevance
“…It was shown that the U6 intramolecular stem loop from the U6 spliceosomal snRNA has a pH dependent conformational equilibrium that involved helical movement of *258 and base flipping of U80. 81 A recent 13 C T 1 power dependence analysis of this system revealed the presence of a global conformational transition at a rate of about 84 s, that was consistent with the conversion between pH dependent states. 67 Concerning DNA, to date only the terminal residues have displayed flexibility among the oligonucleotides that have been studied.…”
Section: Studies Of Nucleic Acid Dynamics By 13 C Nmrsupporting
confidence: 61%
“…It was shown that the U6 intramolecular stem loop from the U6 spliceosomal snRNA has a pH dependent conformational equilibrium that involved helical movement of *258 and base flipping of U80. 81 A recent 13 C T 1 power dependence analysis of this system revealed the presence of a global conformational transition at a rate of about 84 s, that was consistent with the conversion between pH dependent states. 67 Concerning DNA, to date only the terminal residues have displayed flexibility among the oligonucleotides that have been studied.…”
Section: Studies Of Nucleic Acid Dynamics By 13 C Nmrsupporting
confidence: 61%
“…The overall thermodynamic stability and/or structural properties of some RNAs are influenced by pH (Durant and Davis 1999;Nixon and Giedroc 2000;Bayfield et al 2004;Reiter et al 2004). For example, formation of a protonated A + dC base pair in the anticodon stem-loop of tRNA Lys,3 stabilizes the hairpin structure (Durant and Davis 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many cases of shifted acidities and basicities of nucleobases in nucleic acid structures are known. [154][155][156][157][158][159][160][161][162][163][164][165] One way to strongly influence pK a values, the geometry, and other fundamental properties of nucleotides are bound metal ions and other fixed charges. 66,75,102,153 In particular, the effects of metal ions on acidity of nucleotide functional groups has been quantitatively investigated in nucleobase model systems.…”
Section: Switching Charge Types In Proteins: Metals For Lysine and VImentioning
confidence: 99%
“…One of the most common types of pK a shift found in complex RNA structures involves the N1 moiety of protonated A + ·C base pairs. [154][155][156][157][158][159][160][161][162][163] There are two such A + ·C pairs in the extended U6 internal stem loop of spliceosomal i.e. raised by more than 2 log units.…”
Section: Additional Reasons For Pk a Shifts In Nucleobasesmentioning
confidence: 99%
See 1 more Smart Citation